Corrigendum to “Experimental and Nitta–Chao model prediction of high pressure density of p-xylene with dialkyl carbonates or n-alkanes" - Gayol, Ana (2015)
It has come to our attention that in our paper published in The Journal of Chemical Thermodynamics (J. Chem. Thermodyn. 69 (2014) 193-?200), the density values for the composition x1 = 0.8031 of (n-octane (1) + p-xylene (2)) binary system are misprinted in table 6 for all temperatures evaluated. This also affects figure 2b and table 8 for the modified Tait equation coefficients.